Vapour, gas, dust and fume occupational exposures in male patients with rheumatoid arthritis resident in Cornwall (UK) and their association with rheumatoid factor and anti-cyclic protein antibodies: a retrospective clinical study. Issue 5 (17th May 2018) - Murphy, Dan; Bellis, Katy; Hutchinson, David
Abstract : Objectives: To quantify exposure to vapour, gas, dust and fumes (VGDF) and smoking in male rheumatoid arthritis (RA) and investigate impact on rheumatoid factor (RF) and anti-citrullinated protein antibody (ACPA) levels. Design: A retrospective observational study. Setting: The Royal Cornwall Hospital Trust, UK. A single university hospital setting. Participants: 726 men followed up between February 2015 and August 2016, fulfilling RA diagnostic criteria. Main outcome measures: Prevalence of VGDF exposure and smoking prior to RA diagnosis. Determination of association between VGDF, smoking and autoantibody levels. Results: 546/726 (75%) had been exposed to VGDF for >1 year. 561/726 (77%) had been smokers. Only 58/726 (8%) had no exposure to VGDF and had never smoked. A significant difference in RF levels was observed between unexposed and VGDF exposed never smokers (median RF 24 vs 36, p=0.03), more marked when comparing unexposed with ≥2 VGDF exposures (median RF 24 vs 57, p=0.02). A significant difference in RF levels was also observed between unexposed and VGDF exposed smokers (median RF 71 vs RF 95, p=0.04), more marked when comparing unexposed with ≥2 VGDF exposures (median RF 71 vs RF 113, p=0.01). A significant difference in RF titre was observed between never smokers >2 VGDF exposures and smokers with >2 VGDF exposures (RF 57 vs RF 113, p=0.02). No association of ACPA seropositivity rates or titres with VGDF exposure was observed. Smokers with >2 VGDF exposures had a significantly lower age of RA diagnosis than smokers with no VGDF exposure (53 years vs 57 years, p=0.03). All results remained similar when corrected for social class. Conclusions: VGDF exposure increases RF levels. Combination exposure to smoking and VDGF results in higher RF levels, particularly with multiple exposures. These compelling findings demonstrate the importance of combined inhaled exposures in RF generation.